Analyzing the Influence of Managerial Traits and Financial Strategies on Corporate Risk-taking in the Tehran Stock Exchange - Gholamreza Karami; Ali Asghari (تحقیقات مالی)
ObjectiveInvestment is one of the powerful levers to achieve socio-economic growth and development. Since investment is often associated with economic growth and prosperity, it can be expected that ignoring this issue can lead to stagnation or a decline in the company's financial situation. Also, risk is associated with managers when they do not make enough efforts to earn profits and attribute any failure in the company's performance to external factors from control or major shareholders. Therefore, based on this argument, the purpose of the current research is to investigate the impact of management characteristics and financial strategies on the risk-taking of companies listed on the Tehran Stock Exchange. MethodsThis research is applied in terms of the type of objective and post-event in terms of the experimental research method. In terms of the reasoning method, this research is a type of inductive research that uses the observation of parts of the society (sample) to present a model for the whole society. The current research is theoretically among the proof researches and statistically, it is a correlational study that multivariable linear regression is used to test the research hypotheses. The quantitative data needed to test the research hypotheses were extracted from the audited financial statements published in the publishers' comprehensive information system (Kedal Network) and Rahvard Novin software. The socio-statistics studied in this research included all the companies admitted to the Tehran Stock Exchange during the years 2013 to 2021. ResultsThe results obtained from the first hypothesis showed that the characteristics of management (management ability, management overconfidence, political connections, and power of the CEO) reduce the company's risk-taking. Also, the result of the second hypothesis of the research indicates that financial strategies (working capital strategy, investment strategy, and profit-sharing strategy) reduce corporate risk-taking. ConclusionIn strategic management research, several factors can influence the company's risk-taking, one of which is the characteristics or personality of managers, as well as other factors such as financial strategies. Also, the behavior of managers can lead to different decisions that affect the company and investors. In this regard, the results obtained from the first hypothesis of the research indicated that managerial characteristics reduce the companies' risk-taking. This means that the more a company's managers have high personality traits (for example, capable managers or powerful managers and managers with high politics), they reduce the company's risk for shareholders through their abilities. Considering the second hypothesis of the research, it can be stated that financial strategies have an impact on the companies' risk-taking. Valuation of companies is a necessity of planning for managers and investors. Valuation shows how the strategy and financial structure affect the stock market value of companies. The value of the company is very important for the shareholders, investors, managers, creditors, and other stakeholders of the company in their evaluation of the future of the company and its impact on the estimation of risk and return on investment and stock price. Thus, the acquired outcome suggests that, from a strategic management perspective, financial strategies that establish long-term company goals, make informed decisions aligned with these objectives, and allocate resources accordingly can also mitigate the company's risk exposure by overseeing projects with a net negative impact on the organization. Therefore, appropriate financial strategies can reduce the corporate risk-taking.